Descriptive analysis of injury types and incidence during futsal preseason across different competitive levels - Marques, Catarina; Rebelo, Miguel; Crisóstomo, Rute; Honório, Samuel; Duarte-Mendes, Pedro; Petrica, João; Serrano, João (Frontiers in Sports and Active Living, 2024)
Introduction This study aimed to verify the typology and incidence of injury by comparing the different competitive levels of futsal during the preseason. Methods The sample consisted of 68 senior male futsal players (24.26 ± 4.63 years). Data were collected using an injury recording grid that examined the affected body part, anatomical region, type of injury, mechanism, and severity. Results It was found that the elite group has the lowest incidence rate of injury (4.8 injuries per 1,000 h of exposure) compared to the sub-elite (11.8 injuries per 1,000 h of exposure) and amateur groups (13.9 injuries per 1,000 h of exposure). However, at this level, there is the highest percentage of injury occurrence (38.5%), the lower limb was the most affected part of the body (30.8%), and ligament (23.1%) and muscle (15.4%) injuries are the most prevalent. The most frequent mechanism of injury was non-traumatic (30.8%), and the majority were moderate injuries in the elite (23.1%) and sub-elite (17.9%) groups and severe injuries in the amateur group (12.5%). Discussion The amateur futsal players had the highest incidence of injury during the preseason period compared to the other competitive levels. Still, it was at the elite level where the highest percentage of injuries occurred, most of them non-traumatic and of ligament origin, primarily affecting the ankle region. The results highlight the importance of adopting specific injury prevention programs for ligament and muscle injuries during the preseason phase, regardless of the competitive level.